Increased Atp and Ado Overflow from Sympathetic Nerve Endings and Mesentery Endothelial Cells Plus Reduced Nitric Oxide Are Involved in Diabetic Neurovascular Dysfunction - Garcia Huidobro-Toro, J; Mascayano-Collado, C; Donoso-Gomien, M (Frontiers Media S.A., 2018)
Since the mechanism of human diabetic peripheral neuropathy and vascular disease in type 1 diabetes mellitus remains unknown, we assessed whether sympathetic transmitter overflow is altered by this disease and associated to vascular dysfunction. Diabetes was induced by streptozotocin (STZ)-treatment and compared to vehicle-treated rats. Aliquots of the ex vivo perfused rat arterial mesenteric preparation, denuded of the endothelial layer, were collected to quantify analytically sympathetic nerve co-transmitters overflow secreted by the isolated mesenteries of both groups of rats. Noradrenaline (NA), neuropeptide tyrosine (NPY), and ATP/metabolites were detected before, during, and after electrical field stimulation (EFS, 20 Hz) of the nerve terminals surrounding the mesenteric artery. NA overflow was comparable in both groups; however, basal or EFS-secreted ir-NPY was 26% reduced (p < 0.05) in diabetics. Basal and EFS-evoked ATP and adenosine (ADO) overflow to the arterial mesentery perfusate increased twofold and was longer lasting in diabetics; purine tissue content was 37.8% increased (p < 0.05) in the mesenteries from STZ-treated group of rats. Perfusion of the arterial mesentery vascular territory with 100 μM ATP, 100 nM 2-MeSADP, or 1 μM UTP elicited vasodilator responses of the same magnitude in controls or diabetics, but the increase in luminally accessible NO was 60-70% lower in diabetics (p < 0.05). Moreover, the concentration-response curve elicited by two NO donors was displaced downwards (p < 0.01) in diabetic rats. Parallel studies using primary cultures of endothelial cells from the arterial mesentery vasculature revealed that mechanical stimulation induced a rise in extracellular nucleotides, which in the cells from diabetic rats was larger and longer-lasting when comparing the extracellular release of ATP and ADO values to those of vehicle-treated controls. A 5 min challenge with purinergic agonists elicited a cell media NO rise, which was reduced in the endothelial cells from diabetic rats. Present findings provide neurochemical support for the diabetes-induced neuropathy and show that mesenteric endothelial cells alterations in response to mechanical stimulation are compatible with the endothelial dysfunction related to vascular disease progress. © 2018 Donoso, Mascayano, Poblete and Huidobro-Toro.